2012
DOI: 10.5941/myco.2012.40.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ethanol Extracts fromNurukon Oxidative Stress, Melanogenesis, and Photo-Aging

Abstract: Nuruk contributes to the unique characteristics of Korean alcoholic beverages. In this study, the effects of nuruk extracts (NE) on anti-oxidant characters, melanogenesis, and anti-photoaging activity were investigated. NEs were obtained from the 70% ethanol extracts of six types of nuruk, which have been used in brewing of fermented alcohol beverages in Korea. First, various antioxidant characteristics were identified in terms of 2,2'-azino-bis(3-ethylbenzthiozoline-6-sulphonic acid) (ABTS) radical scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…Previous studies have also demonstrated that major antioxidant enzymes such as catalase, superoxide dismutase (SOD), and glutathione peroxidase (GPx) protect UV-induced oxidative effects. Among these antioxidant enzymes, catalase is a representative epidermal differentiation marker in redox damage, and it acts to reduce photooxidative stress (18). In the present study, KPE significantly increased catalase protein levels (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have also demonstrated that major antioxidant enzymes such as catalase, superoxide dismutase (SOD), and glutathione peroxidase (GPx) protect UV-induced oxidative effects. Among these antioxidant enzymes, catalase is a representative epidermal differentiation marker in redox damage, and it acts to reduce photooxidative stress (18). In the present study, KPE significantly increased catalase protein levels (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Nuruk, a traditional Korean fermentation starter for beverages, shows radical scavenging activity (31). It contains 2,6-dimethoxy-p-benzoquinoe.…”
Section: Future Directionsmentioning
confidence: 99%
“…주박은 쌀, 물, 누룩, 효모 등을 이용하여 청주나 약주를 빚 은 후 술을 걸러내는 과정에서 생성되는 부산물이다 [5]. 양조 과정 중에 첨가되는 주박 미생물들은 균 자체로서 풍부한 영 양분을 함유하고 있다 [11]. 현재 우리나라에서 주박은 폐기물 관리법에 의해 산업폐기물로 지정되어 있으며, 양돈업자에 의 해 사료용으로 소비되거나 추가비용을 들여 폐기하는 실정이 다.…”
Section: 서 론unclassified